2017
DOI: 10.15346/hc.v4i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of non-monetary reimbursement for participants in HCI research

Abstract: When running experiments within the field of Human Computer Interaction (HCI) it is common practice to ask participants to come to a specified lab location, and reimburse them monetarily for their time and travel costs. This, however, is not the only means by which to encourage participation in scientific study. Citizen science projects, which encourage the public to become involved in scientific research, have had great success in getting people to act as sensors to collect data or to volunteer their idling c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Resultant transcripts were over 80,000 words long in total. Participants volunteered their time out of interest for the project rather than for fiscal compensation, which research has suggested leads to higher quality data (Wiseman, Cox, Gould, & Brumby, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Resultant transcripts were over 80,000 words long in total. Participants volunteered their time out of interest for the project rather than for fiscal compensation, which research has suggested leads to higher quality data (Wiseman, Cox, Gould, & Brumby, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Wiseman et al demonstrated the feasibility and effectiveness of HCI research with participation of citizen scientists. They found that data provided in the absence of monetary reward, and contributed for altruistic reasons, can equal or indeed exceed the quality of data generated by paid participants [34]. Their results suggest that citizen science can provide viable solutions for large scale HCI experiments that could be otherwise prohibitively expensive to run.…”
Section: Related Work Citizen Science and Data Privacymentioning
confidence: 97%
“…Researchers often tell people something about themselves in exchange for their participation in research studies [34], [29]. This kind of quid pro quo is an effective way of recruiting new and curious 'citizen scientists' who help to improve our understanding of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Factors besides money can also be the primary motivation for participants. In previous work we have explicitly compared monetary and non-monetary reimbursement for participants (Wiseman et al, 2017). One of the things we wanted to study was whether participants could be motivated by being given data about themselves as an outcome of a study.…”
Section: Payment and Non-monetary Remunerationmentioning
confidence: 99%
“…This has produced some very large snowballed samples, where participants recruit other participants. In Wiseman et al (2017), we compared this kind of data-as-reward approach with other approaches, like simply requesting help for the good of science or in return for payment. We found that that participants in both non-monetary conditions met, and in many cases exceeded, the performance of participants in our control paid condition.…”
Section: Payment and Non-monetary Remunerationmentioning
confidence: 99%